Legal Force of Final Decisions of the Constitutional Court - I Nyoman Suandika; I Made Suwena; Erikson Sihotang (International Journal of Social Service and Research, 2026)
The problem addressed in this research is what rationale underlies the granting of permanent legal force to Constitutional Court decisions since they are pronounced in a public plenary session. This research employs a normative legal research method using statutory, conceptual, historical, and comparative approaches. The legal materials used consist of primary, secondary, and tertiary legal materials. The technique for collecting legal materials is conducted through document studies, while the technique for analyzing legal materials is descriptive-analytical. The results of the study show that the rationale underlying the granting of permanent legal force to Constitutional Court decisions after they have been pronounced in a public plenary session is that cases submitted to the Constitutional Court are related to state administration, requiring prompt decisions and being subject to time constraints to prevent disruption to the continuity of other state administration agendas. The possibility of conducting a judicial review of Constitutional Court decisions, viewed from a normative perspective, is not available because Article 47 of the Undang-Undang Mahkamah Konstitusi confirms that Constitutional Court decisions obtain permanent legal force once they are pronounced in a public plenary session. This principle is further emphasized in the explanation of Article 10 paragraph (1), which states that permanent means that no further legal action can be taken.